Применение метода многомасштабного моделирования для исследования электрического поля в изоляции силового кабеля на 330 кВ в аварийном режиме - Кучерявая, И.Н. (Технічна електродинаміка, 2012)
The distributions of electric field in the cross-section of 330 kV cable with cross-linked polyethylene insulation in emergency operation are obtained by computer modeling. The modeling is carried out using Comsol and finite-element method. The approach of multi-scale modeling and concept of elementary unit of structure are used. The computations and investigation are realized for different frequency of applied voltage and possible values of conductivity of semiconductive layers.